COMPARISON BETWEEN COOPERATIVE LEARNING METHODS AND PROBLEM BASED LEARNING USING PERSONAL LETTER IN TEACHING STUDENTS’ ABILITY IN WRITING AT SMA SEBELAS MARET BANDUNG - Verawati Verawati; Wawan Kuswandi (IKIP Siliwangi, 2020)
The paper explains about the comparison between cooperative learning methods and problem based learning using personal letter in teaching students’ ability in writing skill. Experiment study at SMA Sebelas Maret Bandung. The method of this research is experiment quasi concerning experiment class was given learning treatment by using cocoperative learning methods meanwhile control class was given learning by using problem based learning. Student ability in writing sklill is measure by questionnaire or test. Result of the research peove that student ability in writing who teach by cooperative learning methods same as the student who teach problem based learning. The T’test means that the null hypothesis accepted, there is no difference in the ability of the initial writing of the experimental class and the control class. Some difficulties of students; lack of vocabulary, can’t write content is well, hard to understand the topic, hard to answer the question, and still nervous during discussion. To solve the problems like that the teacher can be a solution. Keywords: Cooperative Learning Methods, Problem Based Learning, Writing